INCIDENCE AND RISK FACTORS FOR ACUTE KIDNEY INJURY IN INTENSIVE CARE UNIT PATIENTS, A SINGLE CENTER STUDY IN SULAIMANIYAH - Jalal, Shakar Jamal; Al-Mukhtar, Safa Ezzadin; Amin, Kawa Hussain (Journal of Sulaimani Medical College, 2024)
Background Although there is marked progress in the quality of critical care, there is still an increase in the incidence and mortality of Acute Kidney Injury (AKI) in patients admitted to the Intensive Care Unit. We conducted a single-centre prospective study to evaluate the importance of Acute Kidney Injury in the intensive care unit (ICU) in Sulaimaniyah. Objectives The study aimed to know the frequency of patients who suffer from Acute Kidney Injury after being admitted to the Intensive Care Unit in Shar hospital Sulaimaniyah City to identify the important risk factors for Acute Kidney Injury. Patients and Methods In this prospective cohort study conducted on 210 patients admitted to Shar hospital/ICU between October 2020 to October 2021, we monitored the patients for up to 30 days after ICU admission. Characteristics and outcomes were compared between AKI and non-AKI groups, renal replacement therapy (RRT) and non-RRT patients. Results A total of 210 patients were included in the fi nal analysis; the incidence of AKI was 39% in which stage 1(8.2%), stage 2(16.7%), stage 3(19.2%), among patients with AKI 43.7% of them referred to the nephrologist, and 12.2% received RRT, continuous renal replacement therapy with post-dilution mode and unfractionated heparin for anticoagulation alone was the most frequent mode of RRT (8 patients out of 10). Complete renal recovery, partial recovery, and death were observed in 47.6%,12.2% and 40.2%, respectively. Conclusion Our study showed that Acute Kidney Injury is highly prevalent in ICU patients and associated with high morbidity and mortality
Keywords: Acute Kidney Injury; Intensive Care Unit; KDIGO; Renal Replacement Therapy